Historical studies in the physical sciences. - McCormmach, Russell (Princeton University Press, 1975)
Historical Studies in the Physical Sciences is a continuing series of volumes comprising articles that elucidate the intellectual and social history of the physical sciences from the eighteenth century to the present. The articles offered in Volume 5 share a common theme: a concern with modern physics and its relation to other scientific disciplines and to its cultural and material context.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Physics -- History -- 19th century.; Physique -- Histoire -- 19e siècle.; SCIENCE -- General.; SCIENCE -- Energy.; SCIENCE -- Mechanics -- General.; SCIENCE -- Physics -- General.; Physics; 1800-1899; History